2019
DOI: 10.1016/j.aott.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of postural stability in women with hip osteoarthritis: A case–control study

Abstract: ObjectiveThe aim of the study was to assessment the impact of hip osteoarthritis on postural stability.MethodsOne hundred and twenty-five randomly selected women 20–85 years old (mean age of 49 ± 24.4 years) were assigned to three groups based on age, health status and activity level. Group 1 (cases) – elderly women with diagnosed hip osteoarthritis, group 2 (control) - women without hip osteoarthritis, and group 3 (control) - healthy young women. Assessment of postural stability were measured using a WIN-POD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Lord reported in a sample of 95 elderly individuals that postural stability is signi cantly associated with decline in proprioception and vibration sense of the lower extremity [10]. Slomka reported that the generalized sensomotor de cit, a lack of proprioceptive information, and loss of neuromuscular control due to the degenerative process may lead to balance problems in osteoarthritis patients [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lord reported in a sample of 95 elderly individuals that postural stability is signi cantly associated with decline in proprioception and vibration sense of the lower extremity [10]. Slomka reported that the generalized sensomotor de cit, a lack of proprioceptive information, and loss of neuromuscular control due to the degenerative process may lead to balance problems in osteoarthritis patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan reported the existence of an age-related change in proprioception and static joint position sensation in women and provides a basis for further investigation of contributory factors of musculoskeletal trauma in the elderly [4]. Studies have also reported that postural stability is associated with joint position sense [10] and that patients with hip osteoarthritis have impaired joint position sense, which affects their posture and body balance [11]. When the joint capsule and joint…”
Section: Introductionmentioning
confidence: 99%
“…In addition to gait impairments, several studies have shown impairments in postural control in people with HOA ( Truszczyńska et al, 2016 ; Picorelli et al, 2018 ; Slomka et al, 2019 ), which have partly been attributed to a loss of proprioception ( Slomka et al, 2019 ). Proprioception strongly relies on the afferent information of a group of mechanoreceptors ( Gardner, 2021 ), of which there is a significantly lower number in the hip joint capsule, labrum and femoral head ligament of people with HOA ( Moraes et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SLS test was found to be correlated with the strength of the gluteus medius 6) , the quadriceps, the hamstrings 7) , and the plantar flexors 8) . On the other hand, SLS was affected by somatosensory information 9,10) . In this context, previous studies reported that SLS was affected by vibration and tactile sensitivity 11) and that the triceps surae muscles could alter the perception of the ankle joint position 12) .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, previous studies reported that SLS was affected by vibration and tactile sensitivity 11) and that the triceps surae muscles could alter the perception of the ankle joint position 12) . Moreover, it has been indicated that the lack of proprioceptive information in hip OA patients leads to a loss of neuromuscular control 9) . It is believed that the SLS test for hip stability assessment adjusts for the effect of lower extremity muscle activity 10,13) and somatosensory perception 11,12) .…”
Section: Introductionmentioning
confidence: 99%